2022
DOI: 10.3390/mi13091377
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Microfluidic Bioreactors Used for the Preferential Growth of Bacterial Biofilms through Dielectrophoresis

Abstract: A realistic modelling of the way biofilms form and evolve in time requests a dynamic approach. In this study, the proposed route uses continuous-flow bioreactors under controlled flow rates and temperature in the culture medium containing bacteria or fungi. 3D printed, Polylactic acid (PLA), flow-based bioreactors with integrated copper electrodes were used to investigate the effect of dielectrophoresis on the formation and growth of Staphylococcus aureus ATCC 25923, Enterococcus faecalis ATCC 29212, Pseudomon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The SEM images for the biofilm formed inside the microfluidic devices ( Figure 7 ) presents more disorganized structures, with defined colonies, but no identifiable singular cells. This phenomenon could be explained by the experimental conditions, such as the sheer stress and flow rate present inside the microfluidic channels [ 24 ]. Another noticeable aspect is the arrangement of the colonies along the deposition lines for the Enterococcus and Klebsiella biofilms, with cervices between the filaments, and small connection areas between colonies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SEM images for the biofilm formed inside the microfluidic devices ( Figure 7 ) presents more disorganized structures, with defined colonies, but no identifiable singular cells. This phenomenon could be explained by the experimental conditions, such as the sheer stress and flow rate present inside the microfluidic channels [ 24 ]. Another noticeable aspect is the arrangement of the colonies along the deposition lines for the Enterococcus and Klebsiella biofilms, with cervices between the filaments, and small connection areas between colonies.…”
Section: Discussionmentioning
confidence: 99%
“…As can be observed in the OCT images ( Figure 5 ), the deposition of biofilm inside the microfluidic devices is not uniform along the length of the channel, due to process parameters such as sheer stress and flow rate, which can lead to an irregular detachment of the biofilm. The thickness of the biofilm can vary both depending on the type of bacteria and its capacity to form biofilms, as well as on the investigated area (with thicker biofilm layers visible closer to the entrance and towards the center of the channels, and thinner layers towards the end of the channel [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, STRs are suitable for use with shear-resistive microorganisms. Furthermore, Csapai et al [42] compared the effects of flow and electric field on biofilm formation in a microfluidic device, and found that biofilms grown under static conditions were well defined compared to biofilms subjected to the low flow rate of 0.1 mL/min (Reynold's number of 1.49 and flow velocity of 0.69 mm/s). The fluid flow conditions and flow parameters used in some biofilm studies are summarized in Table 2.…”
Section: Influence Of Fluid Dynamics On Biofilm Formationmentioning
confidence: 99%